Study of Cytomorphological Patterns of Neoplastic Breast Lesions along with Robinson’s Cytological Grading of Invasive Ductal Carcinoma - ., Malashree; Umapathy, Gowda Kavita; P, Shashikala (Annals of Pathology and Laboratory Medicine, 2024)
Background Fine Needle Aspiration Cytology (FNAC) plays an important role as it is a simple, minimally invasive, cost-effective, outpatient-based, and rapid diagnostic method. Grading of breast carcinoma is ideal as it helps in the selection of patients for appropriate therapy. The study was undertaken to observe the cytomorphological patterns of neoplastic lesions, assess the grade of invasive ductal carcinoma by Robinson’s cytological grading, and to correlate with Modified Bloom Richardson’s histopathological grading wherever possible. Material and Methods A descriptive cross-sectional study was conducted over a period of 2 years (July 2015-June 2017). FNAC of neoplastic breast lesions was studied. Invasive ductal carcinomas were graded according to Robinson’s cytological grading system and compared with Modified Nottingham Bloom-Richardson’s histological grading in instances where resected specimens were available. Results In the present study, fibroadenoma (31/33; 94.0%) was the most common benign neoplasm and invasive ductal carcinoma (40/41; 97.6%) was the most common malignant neoplasm. According to Robinson’s cytological grading done on IDC breast, the majority of the cases were grade II [24 (60.0%)]. Histopathological correlation was done by Modified Bloom Richardson’s grading on 13 cases of IDC in which 6 (42.8%) cases were in grade II followed by grade III and I. There was a significant concordance of 71.4% (p=0.015) between Robinson’s cytological grading system and Modified Nottingham Bloom Richardson’s histopathological grading system. Conclusion Robinson’s cytological grading on invasive ductal carcinoma of the breast has good concordance with Modified Bloom Richardson’s histopathological grading.